Addition of various types and levels of vegetable oil on the physical quality of Mozzarella cheese - Hariyadi, Farah; Purwadi, Purwadi; Thohari, Imam (Universitas Halu Oleo, 2023)
This study aims to prove that adding various types and levels of vegetable oil has good characteristics in terms of physical quality. The research material was fresh bovine milk, starter cultures, citric acid, rennet, sodium citrate (Na₃C₆H₅O₇), and vegetable oil. The method used is a laboratory experiment using a nested, Completely Randomized Design (CRD). Treatment A, namely the type of vegetable oil, and treatment B, namely the level of vegetable oil. Data analysis used analysis of variance (ANOVA), followed by Duncan's Multiple Range Test (DMRT) if the results showed a significantly different or highly significant effect. The results showed that the addition of vegetable oil (treatment A) had no significant effect (P>0.05) on pH, color (L*a*b*), stretchability, reliability, elasticity, hardness, and free oil. The level of vegetable oil nested in the type of vegetable oil (treatment B) had a highly significant effect (P